EFFECTIVENESS OF DOUBLE-J STENTING FOR HYDRONEPHROSIS DUE TO PREGNANCY: A SINGLE CENTRE EXPERIENCE - Ghani, Azra A; Ahmad, Bilal (Journal of Postgraduate Medical Institute, 2017)
Objective: To determine the effectiveness of double-J stenting for hydronephrosis during pregnancy. Methodology: This study was conducted at the Department of Urology, Lady Reading Hospital, Peshawar. Study design was observational and the duration of the study was 2 years from January 2015 to December 2016 in which a total of 50 patients were observed. Women with antenatal hydronephrosis (grade 2 or above), before 32 completed weeks of gestation and 20-40 years of age were included. All women were subjected to double-J stent insertion under local anesthesia by single experience surgeon. After insertion of the stents, all women were kept in the ward for further evaluation and discharged if stable on 2nd post operative day. All women were regularly followed up and a check ultrasound were done at the end of 1st month of treatment to determine the effectiveness in terms of improvement in at least 2 grades of hydronephrosis from baseline. RESULTS: Mean age was 28 ±4.16 years. On presentation, 23(46%) patients had grade 2 hydronephrosis, 17(34%) had grade 3 hydronephrosis and 10(20%) had grade 4 hydronephrosis. The effectiveness of double-J stenting for hydronephrosis during pregnancy was 72%. CONCLUSION: Double-J ureteral stenting is an effective method in treating hydronephrosis during pregnancy.